An exploratory survey of soybean production in Ayepe, Nigeria - Baten, M.A.; Agboola, A.A.; Mutsaers, H.J.W. (1992)
In 1988 a field survey was conducted on soybean (Glycine max) production trials at Ayepe in Nigeria. The survey investigated yield variability, fertilizer requirements and economic returns among small farmers. It revealed that the soybean yield was low (524 kg/ha), while yield variability was extremely high (from less than 1 50 kg/ha to over 1500 kg/ha). It also showed that available phosphorus in the soil was below the critical level. The survey results indicated that the main factor affecting yield was farmers' experience, followed by soil characteristics and plant population, and that, if these factors were favourable, the gross margin could exceed Naira 4000/ha.